1996
DOI: 10.1161/01.hyp.27.5.1153
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin Adrenocortical Secretagogue Effect Is Mediated by the B Receptor in Rats

Abstract: We investigated the gene expression and localization of endothelin-1 (ET-1) receptor subtypes ET(A) and ET(B) in the rat adrenal cortex as well as their involvement in the corticosteroid secretagogue effect of ET-1 in vitro. Reverse transcription-polymerase chain reaction with primers specific for ET(A) and ET(B) cDNAs demonstrated the expression of both receptor genes in homogenates of adrenocortical tissue. However, in isolated zona glomerulosa and zona fasciculata cells, only ET(B) mRNA was detected. Autora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 37 publications
7
53
0
1
Order By: Relevance
“…It has been shown that ET-1 stimulates plasma corticosterone levels associated with a stress response (35) and that stimulation of the ET B receptor mediates the release of corticosterone from the adrenal cortex (2,46). Our data show that Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ET-1 stimulates plasma corticosterone levels associated with a stress response (35) and that stimulation of the ET B receptor mediates the release of corticosterone from the adrenal cortex (2,46). Our data show that Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have linked ET-1 and attenuation of sympathetically mediated responses; specifically, our laboratory has shown that ET A receptor activation attenuates the acute stress-induced pressor response (10). In addition, both ET receptor subtypes have been implicated in triggering the release of corticosterone (2,46). Some rodent models display acute stress-mediated corticosterone release; thus, alterations in the expression or function of the ET pathway may be involved in the regulation of shortand/or long-term stress responses.…”
mentioning
confidence: 99%
“…ZG was separated from inner zones by gently stripping the gland capsule, and dispersed ZG and ZF/R cells were obtained by sequential collagenase digestion and mechanical disaggregation (17). Dispersed cells were suspended in DMEM containing 100 U/ml penicillin and 100 µg/ml streptomycin, and 0.6 µg/ml ODNs in ETR vehicle, and plated in 35-mm tissue culture dishes.…”
Section: In Vitro Culturementioning
confidence: 99%
“…It, therefore, seemed worthwhile to investigate by reverse transcription (RT)-polymerase chain reaction (PCR) the expression of galanin receptor mRNA in adrenocortical cells, and to address the subtype(s) of receptor involved in the glucocorticoid-secretagogue action of galanin by the selective immuno-blockade of GAL-R1, GAL-R2 or GAL-R3. (24,25). Some mixed zona glomerulosa/ inner cell preparations were also prepared.…”
Section: Introductionmentioning
confidence: 99%